Effectiveness of Autogate Usage in Improving Immigration Services at I Gusti Ngurah Rai Airport - Muhammad Gilang Jaya Sudarmo; Ida Ayu Putu Sri Widnyani; I Gede Wirata (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The use of autogates at I Gusti Ngurah Rai Airport has proven effective in improving immigration services by speeding up the inspection process to 15-25 seconds per passer, reducing queues, and increasing comfort and security through accurate biometric technology. Throughout 2024, more than 4 million passengers, primarily foreign and business tourists, used autogates with a positive response, although manual services are still provided under certain conditions. Obstacles such as limited infrastructure, technologically proficient human resources, and e-passport compatibility remain, but optimal solutions include strengthening technology, user education, human resource development, and adjusting data protection regulations. Integration with national databases and AI technology also optimizes efficiency and security, making autogates a strategic innovation in immigration public services in Indonesia. With a descriptive-analytical approach, this study is expected to provide a comprehensive overview of the legal and regulatory challenges faced, as well as strategic recommendations for the analysis of autogate services at I Gusti Ngurah Rai International Airport by the Class I immigration office specifically for TPI Ngurah Rai. Keywords: Autogate, Immigration, Airport